Edukasi Postur Tubuh untuk Nyeri Punggung Bawah di Posyandu Lansia Wulandari - Panandita, Aulia Marsha; Pristianto, Arif; Arianto, Yusuf (Penerbit Goodwood, 2024)
urpose: Elderly are in the last phase of growth and experience a natural aging process characterised by changes in anatomy, physisiology and psychology, putting them at risk of low back pain. This community service activity aims to increase elderly knowledge related to low back pain, especially how to prevent it through good and correct posture and exercises at home to reduce the symstoms experienced. Methodology: The method given in this counselling activity uses lecture and demonstration methods through poster media. The activity was held on September 28, 2023 at Pos Lansia Sehat Kelurahan Timuran, Surakarta. Evaluation was carried out using a questionnaire before and after the provision of extention materials. Results/findings: Based on the results of the questionnaire evaluation, the average value is 41% and respondents can only answer correctly three out of seven statements. This show that there are still many elderly don’t understand about low back pain. At the end of counselling session, an evaluation of the post-test questionnaire showed an increase of 23%. This increase means that the community activities carried out provide an understanding of low back pain to respondents. Limitation: This counseling activity is limited to discussions related to lower back pain which is only explained in general terms so that other things such as body posture and exercises that can be done at home need to be conveyed in more depth. Contribution: Community activities related to low back pain have increase knowledge of the elderly in the posyandu lansia wulandari.